1984
DOI: 10.1111/j.1365-2710.1984.tb01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug Information Inquiries—who Asks What and Where Are the Answers?

Abstract: The workload of a local hospital-based drug information centre over a 5-year period was studied and was related to the utilisation of primary reference sources in reply to drug related inquiries.Doctors used the service more often than any other health care professional group and questions relating to drug administration/dosage, choice of drug, adverse effects and pharmaceutical problems accounted for over 50", of the total number of inquiries. Over the study period there was an upward trend in the number of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
3
3
1
Order By: Relevance
“…The most frequently used journals (Lancet, British Medical Journal) are the same as reported in a similar European study [9] (Table 2). It is interesting to note the difference between Europe and the United States.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The most frequently used journals (Lancet, British Medical Journal) are the same as reported in a similar European study [9] (Table 2). It is interesting to note the difference between Europe and the United States.…”
Section: Resultssupporting
confidence: 65%
“…On average, 36% of all investigations referred to primary references. This is similar to other studies, where journals were used as references in 38% [8] and 26% [9], respectively, of all questions.…”
Section: Resultssupporting
confidence: 60%
“…23 Furthermore, several previously published studies have shown that treating physicians utilized most of the drug information services followed by medicine postgraduates. [20][21][22]24 These findings were found to be similar to the findings of the present study where in most of the drug information requests received were from the treating nephrologists followed by medicine postgraduates posted to the nephrology wards. We observed in our study that nephrologists were involved in making decision about the drug therapy for most of the patients.…”
supporting
confidence: 81%
“…In this case, use of tertiary sources like product monographs, textbooks or SPCs would provide quick answers to most of the questions. Whereas we report a median time of 3.0 h to process the answer to a query, Joy et al reported that only 2% of the answers took longer than 90 min to process [7]. Merritt et al reported that only 21% of the queries took more than 60 min to process [4].…”
Section: Discussionmentioning
confidence: 54%
“…The type of literature search needed was categorised as none, simple and complex, meaning that the DIC personnel could give the information and advice from memory, that reference to information sheets or basic texts was necessary or that a detailed bibliographical search had to be performed, respectively [6]. The extent of use of primary reference sources and more subjective methods based on a scale of difficulty rank have also been proposed as surrogate variables to assess the complexity of queries [7, 8]. Furthermore, a high number of drugs in the query could make it more difficult and time consuming to answer.…”
Section: Introductionmentioning
confidence: 99%